ANALISA KADAR LOGAM TIMBAL DAN BESI PADA SUSU KENTAL MANIS KEMASAN KALENG YANG BEREDAR DI KELURAHAN TANJUNG SARI DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Taruli Rohana Sinaga; Sitohang, Rosina; Bemby Sinaga, Arman (Universitas Sari Mutiara Indonesia, 2020)
Sweetened condensed milk is cow's milk in which the water is removed and added sugar, resulting in milk that is very sweet in taste and can last for a year if it is not opened. Sweetened condensed milk products, powdered milk, and sterile milk are often made in packaging made of plastic and cans to avoid the influence of sunlight, packaging time, storage and others. And as a result of the packaging, the product is often damaged either microbiologically, mechanically or chemically. These cans are lined with other coating materials with certain protection. This is to prevent a reaction that could cause the can to corrode and leak. The presence of these metals, even in small levels, will endanger the health of consumers and considering that heavy metals will accumulate in the body, so that gradually the levels will increase and are very dangerous to health, including Pb and Fe metals that can act on the can. Qualitative testing is to determine the presence of the metal present in the sample and quantitative testing is to determine how much content is present in the sample. Before carrying out quantitative testing, the samples were first destroyed using wet destruction. From the results of qualitative testing, all samples contained Pb and Fe metals. From the results of quantitative testing on Pb, the lowest sample was found in sample 3 of 0.0105 mg/kg and sample 5 of 0.0105 mg/kg, this did not exceed the SNI 297.2011 threshold of 0.02 mg/kg. While the results for heavy metal Pb at large concentrations in sample 1 were 0.0239 mg/kg; sample 2 of 0.0371 mg/kg, and sample of 0.0262 mg/kg exceeds the threshold of SNI 297.2011 of 0.02 mg/kg while for heavy metal Fe is still below the threshold allowed by SNI 297.2011 which is 10.0 mg/kg, namely sample 1 of 0.0081 mg/kg; sample 2 of 0.0100 mg/kg; sample 3 of 0.0079 mg/kg; sample 4 is 0.0068 mg/kg and sample 5 is 0.0122 mg/kg.